1966
DOI: 10.1002/1097-4679(196601)22:1<22::aid-jclp2270220106>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of intellectual functioning following unilateral temporal lobectomy

Abstract: INTRODUCTIONAlthough evidence for the presence of lateralized cognitive deficits in man is not unequivocal(8), acute destructive lesions of the dominant cerebral hemisphere have been shown to produce selective verbal impairment while nondominant hemisphere lesions have been associated with visuospatial dysfunction", l a ) . Such differential patterns of psychological test performance have appeared more consistently in cases with lateralized posterior lesions @). Furthermore, the verbal deficits arising out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Again, no references are given to support this contention. It should be noted, however, that several investigators (Meier and French, 1966;Milner, 1954;Reitan, 1955a) have commented that impairment in the ability "to size up a social situation appropriately," as manifested by explicit results on instruments such as the Wechsler Picture Arrangement subtest and the McGill Picture Anomalies Test, is related to nonfrontal rather than frontal lesions.…”
Section: Overview Of the History And Development Of Conclusion Aboutmentioning
confidence: 99%
“…Again, no references are given to support this contention. It should be noted, however, that several investigators (Meier and French, 1966;Milner, 1954;Reitan, 1955a) have commented that impairment in the ability "to size up a social situation appropriately," as manifested by explicit results on instruments such as the Wechsler Picture Arrangement subtest and the McGill Picture Anomalies Test, is related to nonfrontal rather than frontal lesions.…”
Section: Overview Of the History And Development Of Conclusion Aboutmentioning
confidence: 99%
“…9,10 Of concern, one study reported that 2 to 5 years after RTL surgery there is an increasing deficit on a nonmemory perceptual analyses task, suggesting late decline on a task associated with the right hemisphere. 11 Studies of very long cognitive sequelae of surgery are even more rare, 12 with little information available as to the cognitive stability of temporal lobe surgical patients as they age.…”
mentioning
confidence: 99%
“…Since surgical treatment of medically refractory epilepsy can be desirable in certain patients whose seizures are suspected to originate in a focal fashion (for review see, Purpura et al, 1975) and since intellectual status may change for better or worse following the operation (Meyer and Yates. 1955: Meier and French. 1966: Milner, 1975.…”
mentioning
confidence: 99%